MECHANISM MANAGE QUALITY SYSTEMS «HUMAN - TECHNICAL» WORKER PLACES ON ENTERPRISE INDUSTRY TRANSPORT AND TECHNICHAL SERVICES - Petr P. Gladky (Вестник Северо-Кавказского федерального университета, 2022)
Methods of complex certification systems «human - technique» workers places and models management parameters condition workers places and professionals qualification level of workers, are the basis of the mechanism of development management system workers places in enterprises.